Different Modes to Enter India: Case of McDonalds and Coca-Cola - Sodhi, Gursharan Singh (2007)
This research is to discuss the different entry modes used by MNCs to enter international market and what are the factors responsible for choosing the specific mode of entry. This research also shows that why the international companies adopt to the different entry modes for various countries depending on the market conditions. It is observed that in this world of globalization, all the international companies are looking to expand in different parts of the world but with different approaches. I found this very interesting to identify why different companies of similar industry prefer different modes of entry to expand in same market of a country. Therefore, the purpose of this research is to explore the modes of foreign entry used by the multi-international companies and also to relate this study finding with the previous researchers work. In this study, we will have a look at a particular case of McDonalds and Coca- Cola companies from same food and beverages industry expanding in India.